Design and Development of a News Website and CMS Based on Three-Tier Architecture: A Case Study of PLTU Pangkalan Susu - Zainuddin; Veri Ilhadi (Yayasan Kita Menulis, 2026)
Pangkalan Susu Steam Power Plant does not yet have a structured official publication platform, causing information dissemination to depend mainly on social media and making news archives difficult to organize and retrieve regularly. This condition highlights the need for a web-based information system that supports more professional content management. This study aims to design and develop a news website and Content Management System (CMS) by applying a Research and Development (R&D) approach and three-tier architecture, which separates the presentation layer, application logic layer, and data layer. The development process consists of requirements analysis, system architecture and database design, implementation, and functional testing. The system was implemented using Laravel as the application framework, Blade for the user interface, Filament as the administration panel, and MySQL as the database management system. Functional testing was conducted using the black-box method on 14 main scenarios, including the management of news, categories, authors, banners, and logout features. The results show a 100% success rate, indicating that all tested functions operated according to the expected outcomes without functional errors. The proposed architecture produces a modular, scalable, and maintainable system that can support the future development of the official information platform of Pangkalan Susu Steam Power Plant.